Instrumental Activities of Daily Living - Andrzej Klimczuk (The Wiley Blackwell Encyclopedia of Family Studies, 2016)
Activities of daily living are usually defined as skills needed in typical daily self-care. Instrumental activities of daily living (IADLs) are more complex skills beyond basic self-care, and their measurement evaluates how individuals function in their homes, workplaces, and outdoor environments. The skills that pertain to IADLs are exposed to dysfunctions resulting from aging or illness. Reductions in those skills may begin to cause problems with independence but these problems can be solved with the help of others - for example, family members, social workers, and nurses.
Keywords: I10; 330; aging; disability; health care; sociology of health